2007
DOI: 10.1021/ef060471s
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Cracking of Waxes Produced by the Fast Pyrolysis of Polyolefins

Abstract: The cracking of the waxes obtained in the flash pyrolysis of polypropylene has been studied in laboratory FCC units under the standard conditions in FCC (fluid catalytic cracking) units. The reaction equipment is provided with a riser simulator reactor, and the experiments have been carried out using a commercial equilibrium catalyst, with a catalyst/feed ratio of C/O ) 5.5, in the 500-550 °C range and for contact times between 3 and 12 s. The effect of these operating conditions on the yields of products and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 61 publications
0
38
0
3
Order By: Relevance
“…Problems associated with blockage and limited polymer/catalyst contact within the reactor make continuous processing difficult in fixed-bed reactors. Arandes et al [25] performed a fast pyrolysis of PP to obtain waxes that were subsequently degraded in a riser simulator with a commercial FCC catalyst to improve mass-and heat-transfer constraints. At 500-550 8C, mixtures of waxes with vacuum gasoline oils result in a synergetic effect to produce mostly liquefied petroleum gas and gasoline (42 wt%) with about 4-5 wt% coke content.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Problems associated with blockage and limited polymer/catalyst contact within the reactor make continuous processing difficult in fixed-bed reactors. Arandes et al [25] performed a fast pyrolysis of PP to obtain waxes that were subsequently degraded in a riser simulator with a commercial FCC catalyst to improve mass-and heat-transfer constraints. At 500-550 8C, mixtures of waxes with vacuum gasoline oils result in a synergetic effect to produce mostly liquefied petroleum gas and gasoline (42 wt%) with about 4-5 wt% coke content.…”
Section: Tablementioning
confidence: 99%
“…Ultrastable Y (USY) with lower Y framework alumina contents and hence lower unit cell sizes, tend to produce more light alkenes, mainly at the expense of gasoline. A more interesting is that of adding plastic waste into the FCC process, under suitable process conditions with the use of zero value of spent FCC catalysts [21][22][23][24][25] performed on a lab-scale cracking, a large number of polymers can be economically converted into valuable hydrocarbons. Potential concepts have been investigated in our group using a catalytic fluidized-bed reactor to study the product distribution and selectivity of catalytic degradation of several different textiles of post-consumer plastic wastes without PVC mixture previously [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…PPW has a wide application field, which can be used for an abrasion-resistant additive of printing inks, for matting surface coating materials, as base materials for pigment preparation, and as an aid in the processing of plastics (lubricants and release agents), and so on. It can also be a feedstock used by the petrochemical industry for obtaining fuels through pyrolysis or catalytic cracking (Arandes et al, 2007). PPW could be obtained by polymerization of propylene using Ziegler-Natta catalysts and pyrolysis of polypropylene (PP).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies using similar conditions to FCC reactors, it was concluded that cofeeding waxes with vacuum gas oil gives way to an increase in the yield of gasoline (C 5 −C 11 hydrocarbons) and olefins C 2 −C 4 . 26,27 Furthermore, pyrolysis waxes can be co-fed with waxes derived from other processes, such as Fischer−Tropsch, which are also a suitable feedstock for FCC units. 28 This paper studies the upgrading of HDPE pyrolysis waxes in order to obtain light olefins by downstream cracking of the volatile stream (mainly waxes) leaving the CSBR (Figure 1).…”
Section: Introductionmentioning
confidence: 99%